The Influence Of Creating Shared Value (Csv) On Pt Pegadaian Brand Image And Customer Loyalty - Unggul Yoga Ananta; Renny Risqiani; Rully Yusuf (Journal of Social Research, 2024)
This research aims to analyze the influence of creating shared value (CSV) on brand image and customer loyalty at PT Pegadaian. CSV is an independent variable that contains aspects of social, environmental and economic values. CSV performance is focused on PT Pegadaian CSV program, namely sorting waste, saving gold and the gade integrated farming. This research uses an ex post facto quantitative approach with a structural equation model (SEM) which is operated using Amos version 24. Respondents in this research are customers or customers of PT Pegadaian who receive the benefits of the CSV program, namely the waste bank program for sorting waste, saving gold and the integrated gade. farming. Validity testing uses confirmatory factor analysis (CFA) and reliability uses construct measurement values with valid and reliable results. Data analysis uses descriptive statistical analysis and path analysis. The results of the research show that there is a positive and significant influence between social and brand image, there is no significant influence between the environment and brand image, there is a positive and significant influence between the economy and brand image, and there is a positive and significant influence between brand image and customer loyalty. The results of this research provide information that the higher the CSV performance, the more it provides a positive image for the company which influences customer loyalty.